Analisa Dan Perancangan Keamanan Jaringan Lokal Menggunakan Security Onion Dan Mikrotik - Febrison Yohaness; Haeruddin haeruddin (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
With the advancement of technology on this digitalized era, almost every aspect and field has implemented information technology in the work system of companies, yet there are still security gaps that can lead to cybercrime. The purpose of this research is to both provide an analysis and design a system that can prevent and tackle cybercrime issues. The testing method used in this project is Penetration Test on network virtualization and is connected to local network. The end result of this project is a system that is fused with MikroTik software to monitor attacks to the local network. The security system used is Security Onion.